Financial institutions and economic growth of India - Goyal, O.P. (New Delhi : Light and Life Publishers, 1979)
This paper examine economic growth as an integral part of every viable nation across the globe.
Includes index.
Includes bibliographical references: p. 640-648.
asm 24/09/2019
Loans
Keywords: Finance and economic growth; India